2018
DOI: 10.1016/j.coph.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Targeting oxidant-dependent mechanisms for the treatment of respiratory diseases and their comorbidities

Abstract: Oxidative stress is implicated in the pathogenesis of respiratory diseases, such as COPD and its comorbidities, asthma, idiopathic pulmonary fibrosis and radiation pneumonitis. Antioxidants drugs, such as small molecule thiols, nuclear erythroid-2 related factor 2 activators and catalytic enzyme mimetics have been developed to target oxidant-dependent mechanisms. The therapeutic effects of antioxidants have been generally disappointing. A small number of antioxidants are approved for clinical use, such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…Oxidantantioxidant imbalance plays a crucial role in the development of COPD. Oxidative stress caused by smoking and environmental pollution can lead to extensive tissue damage and COPD exacerbation in patients at about 63 years of age [16,17]. Some markers, such as MDA in sputum, appear to be useful for monitoring exacerbation-associated oxidative stress in COPD [18].…”
Section: Oxidation-antioxidant Imbalance Is Involved In the Developmementioning
confidence: 99%
“…Oxidantantioxidant imbalance plays a crucial role in the development of COPD. Oxidative stress caused by smoking and environmental pollution can lead to extensive tissue damage and COPD exacerbation in patients at about 63 years of age [16,17]. Some markers, such as MDA in sputum, appear to be useful for monitoring exacerbation-associated oxidative stress in COPD [18].…”
Section: Oxidation-antioxidant Imbalance Is Involved In the Developmementioning
confidence: 99%
“…Early studies have found that the chronic sustained expression of extracellular SOD (EC-SOD) protects lungs from radiotherapy-induced injury. Therefore, AEOL-10150 is used to treat lung injury after radiotherapy [24]. The results showed that the respiratory rate of Fisher-344 rats increased 8 weeks after radiotherapy (28 Gy), reaching a peak at 18 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to understand the pathology of muscle wasting at a cellular level, since the inherent adaptability of muscle tissue offers nutritional therapeutic options to reverse or delay disease progression (Passey et al, 2016). Oxidative stress is implicated in the pathogenesis of respiratory diseases, including COPD (Thomson, 2018), and is characterised by the release of free radicals, resulting in cellular degeneration that damages cell membranes (Ohira et al, 2008). In patients with COPD, oxidative stress is thought to exacerbate the loss of lean muscle mass, so promotes cachexia (Rawal and Yadav, 2015).…”
mentioning
confidence: 99%